Beluga (Delphinapterus leucas) granulocytes and monocytes display variable responses to in vitro pressure exposures - Thompson, Laura A.; Romano, Tracy A. (Frontiers in Physiology, 2015)
While it is widely known that marine mammals possess adaptations which allow them to make repetitive and extended dives to great depths without suffering ill effects seen in humans, the response of marine mammal immune cells to diving is unknown. Renewed interest in marine mammal dive physiology has arisen due to reports of decompression sickness-like symptoms and embolic damage in stranded and by-caught animals, and there is concern over whether anthropogenic activities can impact marine mammal health by disrupting adaptive dive responses and behavior. This work addresses the need for information concerning marine mammal immune function during diving by evaluating granulocyte and monocyte phagocytosis, and granulocyte activation in belugas (n=4) in comparison with humans (n=4), with and without in vitro pressure exposures. In addition, the potential for additional stressors to impact immune function was investigated by comparing the response of beluga cells to pressure between baseline and stressor conditions. Granulocyte and monocyte phagocytosis, as well as granulocyte activation, were compared between pressure exposed and non-exposed cells for each condition, between different pressure profiles and between conditions using mixed generalized linear models (α=0.05). The effects of pressure varied between species as well by depth, compression/decompression rates, and length of exposures, and condition for belugas. Pressure induced changes in granulocyte and monocyte function in belugas could serve a protective function against dive-related pathologies and differences in the response between humans and belugas could reflect degrees of dive adaptation. The alteration of these responses during physiologically challenging conditions may increase the potential for dive-related in jury and disease in marine mammals.